Reducing the unintended consequence of overfishing due to open access: Learning from the Zamboanga experience - Danilo C. Israel; Milva Lunod-Carinan; Vicente B. Paqueo (Philippine Institute for Development Studies (PIDS), 2016)
The Philippines is blessed with rich marine fishing grounds that are valuable sources of food and livelihood for the population. Unfortunately, over the years, these fishing grounds have become increasingly less productive, and many are in danger of depletion. At the heart of the problem is the generally open-access nature of Philippine fisheries, which leads to the unintended consequence of overfishing. This paper reviews the basic theory of overfishing; institutions, laws, and policies related to overfishing in the Philippines; and past and current efforts to curb overfishing in the country. As case study, it looks into the sardine industry zeroing in on the Zamboanga Peninsula experience. The paper shows how choosing to act collectively in ways that effectively minimize overfishing can keep the sardine industry profitable and sustainable for its participants in the long haul. It also provides some recommendations on how to potentially improve the current situation and make the sardine industry even more effective in addressing overfishing.
Keywords: 330; Sardine; Zamboanga Peninsula; Unintended consequence; Overfishing; Open access; Closed season